2022
DOI: 10.1111/aji.13539
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate mutase 5 promotes necroptosis in trophoblast cells through activation of dynamin‐related protein 1 in early‐onset preeclampsia

Abstract: Objectives: Placentae from patients with preeclampsia have increased susceptibility to necroptosis and phosphoglycerate mutase 5 (PGAM5) plays a role in many necrosis pathways. We determined whether PGAM5 promotes necroptosis of trophoblast cells and the underlying mechanisms in this study. Methods:The injury model was established by treating JEG3 cells with hypoxia for 24 h. The functional measurements were assessed by the cell counting kit-8, propidium iodide (PI)/Annexin V staining, JC-1 staining and firefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…[44] Zhang et al found an upregulation of PGAM5 and increased necroptosis-relevant protein expression in placentae from preeclampsia pregnancies. [45] But Cheng et al found no evidence of necroptosis-associated events in placental tissues from patients with early-onset or late-onset PE. [46] We provide new evidence for the presence of necroptosis and found an increase in the expression of DAMPs molecules in both the human and mice preeclamptic placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Zhang et al found an upregulation of PGAM5 and increased necroptosis-relevant protein expression in placentae from preeclampsia pregnancies. [45] But Cheng et al found no evidence of necroptosis-associated events in placental tissues from patients with early-onset or late-onset PE. [46] We provide new evidence for the presence of necroptosis and found an increase in the expression of DAMPs molecules in both the human and mice preeclamptic placenta.…”
Section: Discussionmentioning
confidence: 99%
“…found an upregulation of PGAM5 and increased necroptosis‐relevant protein expression in placentae from preeclampsia pregnancies. [ 45 ] But Cheng et al. found no evidence of necroptosis‐associated events in placental tissues from patients with early‐onset or late‐onset PE.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs have potent cardioprotective effects in H9c2 cells by inhibiting the Ca2+ overload and the mitochondrial membrane potential dysfunction during hypoxia ( Faridvand et al, 2019 ). Furthermore, there are few studies that evaluated mitochondrial membrane potential in placental trophoblast cells from patients with preeclampsia ( Zhang et al, 2022 ). The anticancer effect of PnDs have not yet been evaluated with the mitochondrial dye JC-1.…”
Section: The Effects Of Perinatal Derivatives On the Hallmarks Of Cancermentioning
confidence: 99%
“…[ 7 9 ] Additionally, levels of cell-derived microparticles (cMPs), released during cell activation or apoptosis, are found to increase significantly in RIF patients. [ 10 ] Moreover, trophoblast necroptosis plays a complex role in pregnancy disorders such as preeclampsia [ 11 , 12 ] and recurrent abortion. [ 13 ] Thus, a potential link exists between RIF and necroptosis, highlighting necroptosis as a promising target for understanding and treating RIF.…”
Section: Introductionmentioning
confidence: 99%